PENGARUH PENAMBAHAN ADSORBEN DAN KULTUR BAKTERI TERHADAP KARAKTERISTIK FESES AYAM RAS PEDAGING - Cokorda Mahardika; Wely Yitro Pello; Yohan Nenomnanu (Politeknik Pertanian Negeri Kupang, 2022)
This study was conducted to investigate the effect of adding adsorbents and cultur bacteria in feces to characteristic of chicken excreta. For each treatment-replication, 150 g of fecal material were collected from the poultry farm and placed in beaker glass. The fecal sample was then treated with 8% activated nature zeolite, 8% carbon active, and 8% bacterial culture Effective Microorganism-4TM and covered with plastic wraps. The temperature and pH were measured after one hour of standing (0 d) and repeated at 48 h intervals for 8 days. Moisture content were measured after one hour of standing (0 d) and 192 hour after incubation. Results indicated that adsorbents with 8% activated nature zeolite, carbon active, and culture bacteria each can reduced the moisture content. The adsorbents had no significant effect on pH and temperature of fecal broilers.Key words: Adsorbents, fecal material, moisture, pH, temperature